(untitled) (Razi Medical Journal, 2025)
The misuse of antibiotics has become a global concern due to their contribution to the development of resistance against these medications. This study aims to assess knowledge, attitudes, and practices regarding antibiotic use among the Libyan population in Tarhuna city. We conducted a cross-sectional study using a validated questionnaire comprising 17 variables among 160 participants from Tarhuna. Results showed that nearly half of the respondents had reported side effects, while more than two-thirds believed they were not experiencing any adverse effects. The majority relied on pharmacists and doctors for information about antibiotics. These medications were mainly used to treat bacterial infections, followed by viral infections, UTIs, and RTIs. Respondents perceived the most common reasons for using antibiotics as resistance and side effects. Many participants believed that misuse of antibiotics could lead to their loss of effectiveness in the future, while a minority were optimistic about their continued efficacy. The study highlights a lack of appropriate attitudes and behaviors leading to antibiotic misuse, emphasizing the need for healthcare institutions to control prescriptions.